Tata Cara Pembayaran Pajak Berdasarkan Ketetapan Pajak - Alvarel David Hutuely; Salmon Eliazer Marthen Nirahua; Heillen Martha Yosephine Tita (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Tax law provisions state that a Tax Assessment Letter is issued if there is an error or non-compliance by the taxpayer.Purposes of the Research: The purpose of this writing is to find out and explain the procedures for paying taxes based on tax assessments.Methods of the Research: This study uses a normative juridical method with the legal materials used in the research are primary, secondary and tertiary and procedures and analysis of legal materials in research through the process of collecting legal materials and then studied, read, reviewed, classified, and analyzed qualitatively.Results of the Research: The procedure for paying taxes is based on SKP in accordance with PMK No. 242/PMK.03/2014 concerning Procedures for Payment and Deposit of Taxes, namely in Article 6, namely that the Tax Assessment Letter must be paid within 1 (one) month from the date of issuance and pay through the service at the counter/teller (over the counter); using other Electronic Systems.